2012
DOI: 10.1186/1471-2458-12-866
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating risk factors for endemic human Salmonella Enteritidis infections with different phage types in Ontario, Canada using multinomial logistic regression and a case-case study approach

Abstract: BackgroundIdentifying risk factors for Salmonella Enteritidis (SE) infections in Ontario will assist public health authorities to design effective control and prevention programs to reduce the burden of SE infections. Our research objective was to identify risk factors for acquiring SE infections with various phage types (PT) in Ontario, Canada. We hypothesized that certain PTs (e.g., PT8 and PT13a) have specific risk factors for infection.MethodsOur study included endemic SE cases with various PTs whose isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…In the fecal E. coli isolates in our study, there was a very low frequency of resistance to cephalosporins, carbapenems, macrolides, and quinolones, which are antimicrobials classified in Canada as being of very high or high importance in human medicine [20]. This is an encouraging finding from a human health viewpoint because flock owners can be exposed to antimicrobial resistant zoonotic pathogens [6,13,15] through direct contact with their birds [10] or their environment [11], or consumption of contaminated meat or eggs [8,9]. However, there was a moderate to high frequency of resistance to tetracycline, streptomycin, sulfonamides, and ampicillin; antimicrobials frequently used to treat bacterial infections in poultry [35].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the fecal E. coli isolates in our study, there was a very low frequency of resistance to cephalosporins, carbapenems, macrolides, and quinolones, which are antimicrobials classified in Canada as being of very high or high importance in human medicine [20]. This is an encouraging finding from a human health viewpoint because flock owners can be exposed to antimicrobial resistant zoonotic pathogens [6,13,15] through direct contact with their birds [10] or their environment [11], or consumption of contaminated meat or eggs [8,9]. However, there was a moderate to high frequency of resistance to tetracycline, streptomycin, sulfonamides, and ampicillin; antimicrobials frequently used to treat bacterial infections in poultry [35].…”
Section: Discussionmentioning
confidence: 59%
“…Non-commercial poultry flocks (denoted as "small flocks") are increasingly popular in urban, suburban, and rural areas in North America [1][2][3]. Small flocks can pose a health risk to their owners by exposing them to zoonotic pathogens [4][5][6][7] through consumption of contaminated meat or eggs [8,9], or direct contact with infected birds [10] or their environment [11]. Antimicrobial resistance (AMR) in zoonotic pathogens adds to this risk [12][13][14][15] because infections with antimicrobial resistant bacteria are more difficult to treat, and result in higher morbidity and mortality [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Subtyping is useful for differentiating between endemic and outbreak cases, especially for common Salmonella serotypes, such as Enteritidis, that occur sporadically throughout the year [ 34 ]. Differences in reservoirs and exposure settings might exist for different S. Enteritidis phage types, and molecular differentiation can help to understand potential sources of the different phage types [ 8 , 34 ]. We defined a cluster as a health region, time period, or a health region during a particular time period with a statistically significant higher than expected phage type-specific S. Enteritidis infection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies conducted in North America have evaluated phage type-specific risk factors for S. Enteritidis infections in humans. In Ontario, Canada, researchers demonstrated that cases with PT 8 were more likely to have had contact with dogs compared to cases with other phage types [ 8 ]. In British Columbia, Canada, a concurrent increase in the incidence of S. Enteritidis infections with PT 8 in humans and the prevalence of PT 8 in poultry was observed between 2007 and 2010 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A case–case approach allows a comparison of symptom severity between pathogens identified in the stool, although it lacks mechanisms to question if a particular pathogen present in the stool is causally related to diarrheal disease. A case–case approach allows restricted and refined analysis of some unique exposures associated with different pathogens detected through a surveillance system 1113…”
Section: Introductionmentioning
confidence: 99%